Omalizumab controls surface phenotypes of dendritic cells and monocytes in asthma - Agnes Yang, BS; Laurie Baert, PhD; Katherine Upchurch, PhD; Mark Millard, MD; Matthew Wiest, PhD; Chao Gu, PhD; HyeMee Joo, PhD; SangKon Oh, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Omalizumab can provide clinical benefits to a fraction of moderate-to-severe asthma patients. However, the mechanisms of action of omalizumab have not been fully understood. Objective: This study investigated whether omalizumab could affect the frequency and surface phenotypes of blood circulating dendritic cell (DC) and monocyte subsets, which could be associated with the mechanisms of action of omalizumab. Methods: Longitudinal analyses of the frequency and surface phenotypes of DC and monocyte subsets in fresh whole blood of moderate-to-severe asthma patients (n = 45, 34 with response and 11 without response, from baseline to week 26) were performed by flow cytometry. Nonasthmatic subjects (n = 22) were also used as controls at baseline. Results: Omalizumab decreased myeloid DC/plasmacytoid DC ratio by increasing the frequency of plasmacytoid DCs. In addition to the decrease of surface FcεRI expression, omalizumab also downregulated HLA-DR, CCR7, and costimulatory molecule expression on both myeloid DCs and plasmacytoid DCs. Omalizumab also decreased CCR7 and HLA-DR expression by monocyte subsets. Omalizumab-mediated reduction of surface CD88 expression on monocytes was associated with asthma symptoms. Conclusion: This study provides new insight into omalizumab’s mechanisms of action. Data from this study will help us understand the roles of serum IgE in shaping surface phenotypes of DCs and monocytes in asthma patients.